Money and the Dispersion of Relative Prices - Hercowitz, Zvi (Journal of Political Economy, 1981)
A price dispersion equation is tested with data from the German hyperinflation. The equation is derived from a version of Lucas's and Barro's partial information-localized market models. In this extension, different excess demand elasticities across commodities imply a testable dispersion equation, in which the explanatory variable is the magnitude of the unperceived money growth. In order to test this hypothesis a price dispersion series is constructed, and a measure of the unperceived part of money growth is estimated. The model receives support from the empirical analysis, although it is evident that unincluded variables have important effects on price dispersion.